2021
DOI: 10.1021/acs.est.0c05125
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target Stoichiometric Binding Identified from Toxicogenomics Explains Why Some Species Are More Sensitive than Others to a Widely Used Neonicotinoid

Abstract: Neonicotinoids are currently licensed for use in 120 countries, making accurate nontarget species sensitivity predictions critical. Unfortunately, such predictions are fraught with uncertainty, as sensitivity is extrapolated from only a few test species and neonicotinoid sensitivities can differ greatly between closely related taxa. Combining classical toxicology with de novo toxicogenomics could greatly improve sensitivity predictions and identify unexpectedly susceptible species. We show that there is a >30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…1 Neonicotinoid insecticides have been registered in over 120 countries, sharing one-fourth of the global insecticidal market. 2 Because of their widespread use and moderate persistence, neonicotinoids are ubiquitous in the environment. 3 Designed to target the post-synaptic nicotinic acetylcholine receptor (nAChR) in invertebrates, neonicotinoids exhibit low acute lethality to vertebrates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Neonicotinoid insecticides have been registered in over 120 countries, sharing one-fourth of the global insecticidal market. 2 Because of their widespread use and moderate persistence, neonicotinoids are ubiquitous in the environment. 3 Designed to target the post-synaptic nicotinic acetylcholine receptor (nAChR) in invertebrates, neonicotinoids exhibit low acute lethality to vertebrates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Agrochemicals are one of the main drivers for degradation of freshwater diversity at a global scale, raising emerging concerns of aquatic risks from current-use insecticides, including neonicotinoids . Neonicotinoid insecticides have been registered in over 120 countries, sharing one-fourth of the global insecticidal market . Because of their widespread use and moderate persistence, neonicotinoids are ubiquitous in the environment .…”
Section: Introductionmentioning
confidence: 99%
“…Still, the species tested in our study, including E. fetida , were very sensitive to copper and imidacloprid, which are known to be toxic compounds for earthworms (see Streit, 1984; Wang et al, 2012). Short et al (2021) exposed different earthworm species to imidacloprid and found that the safety factor proposed by the EFSA did not cover the most sensitive species tested, Amynthas gracilis (KINBERG, 1866). In addition, Frampton et al (2006) performed a pesticide analysis using SSDs and soil invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reduced sensitivity to copper in earthworms from highly acidic soil may be an adaptation to low pH values (<5.5), in which toxic metals such as copper are mobilized (Fernández-Calviño et al, 2008). Moreover, recent studies have used toxicogenomic analysis to investigate and explain why some species are more sensitive to a certain compound (cf., Short et al, 2021). Pesticide uptake in earthworms is mainly through direct contact and oral ingestion (see Short et al, 2021;Streit, 1984).…”
Section: Earthworm Sensitivity and Habitat Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation